Analisis Pengendalian Kualitas Produksi Sandal Menggunkan Pendekatan Six Sigma (Studi Kasus: CV. BOSSBI) - Hardika, Moch Bagus; Munir, Misbach (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
CV BOSSBI is a sandal manufacturing company located in Singosari, Malang, which is currently facing a high number of defective products, impacting both product quality and production efficiency. This study aims to analyze the factors causing product defects and to provide improvement proposals to enhance production quality. The Six Sigma approach using the DMAIC method (Define, Measure, Analyze, Improve, Control) is applied to identify, measure, analyze, and control the causes of defects. Based on production data from January and February 2025, a total of 4,274 defective units out of 90,545 units were recorded in January, and 6,006 defective units out of 87,445 units in February. The initial DPMO (Defects Per Million Opportunities) value was 11,796 with a sigma level of 3.58. After implementing improvements, the DPMO decreased to 7,142 and the sigma level increased to 3.82. The results show that applying the Six Sigma method reduced the defect rate by 39.4% and significantly improved product quality. Therefore, Six Sigma has proven to be an effective quality control strategy for CV BOSSBI. Keywords: CV BOSSBI, DMAIC, Defective Products, Quality Control, Six Sigma